(untitled) (TAJ: Journal of Teachers Association, 2009)
Seventy four patients of pyogenic liver abscess prospectively evaluated by clinical, haematological, microbiological and sonographic methods. The main objective of this study was to find out correlation between intake of indigenous alcohol and to identify class population affected. Most of the affected patients of pyogenic liver abscess are lower and middle class male and who are farmer with mean age 37±11.7 years. Our study reveals ’59 (80%) cases consume that alcohol, among them 56 (95%) patients took locally prepared alcohol (TARI). Organism recovered from pyogenic liver abscess vary considerably. Escherichia coli has been the organism most commonly isolated in our study. 57 cases were treated with ciprofloxacin and sonographic guided needle aspiration. Ciprofloxacin still remains as the drug of choice for this disease and recovery was excellent. So the study reveals that indigenous alcohol is associated with the development of pyogenic liver abscess. doi: 10.3329/taj.v18i1.3299 TAJ 2005; 18(1): 21-24